2016
DOI: 10.2215/cjn.03680316
|View full text |Cite
|
Sign up to set email alerts
|

New Opportunities for Funding Dialysis-Dependent Undocumented Individuals

Abstract: The cost of dialysis for the estimated 6500 dialysis-dependent undocumented individuals with kidney failure in the United States is high, the quality of dialysis care they receive is poor, and their treatment varies regionally. Some regions use state and matched federal funds to cover regularly scheduled dialysis treatments, while others provide treatment only in emergent life-threatening conditions. Nephrologists caring for patients who receive emergent dialysis are tasked with the difficult moral dilemma of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 10 publications
1
44
0
Order By: Relevance
“…In 1972, Congress passed Public Law 92-603, Social Security Amendments of 1972, which mandated Medicare coverage for dialysis for all patients with ESRD who qualified for Social Security benefits or were the spouse or dependent of someone who did. 17 Unfortunately, this coverage did not extend to undocumented immigrants even if they contributed payroll taxes. In certain states, such as Texas, many undocumented immigrants only qualify for emergency dialysis, which is provided only when potentially deadly lab findings or symptoms exist.…”
Section: Managing Undocumented Immigrants' Ckd With Dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…In 1972, Congress passed Public Law 92-603, Social Security Amendments of 1972, which mandated Medicare coverage for dialysis for all patients with ESRD who qualified for Social Security benefits or were the spouse or dependent of someone who did. 17 Unfortunately, this coverage did not extend to undocumented immigrants even if they contributed payroll taxes. In certain states, such as Texas, many undocumented immigrants only qualify for emergency dialysis, which is provided only when potentially deadly lab findings or symptoms exist.…”
Section: Managing Undocumented Immigrants' Ckd With Dialysismentioning
confidence: 99%
“…27 Few immigrants have been able to get coverage for regularly scheduled dialysis under unsubsidized commercial plans, but the sustainability of this option is unknown and still leaves many without coverage. 3 Although emergency dialysis is covered by law, 29 regularly scheduled dialysis is still not the standard of care for most undocumented immigrants in the United States. 30 Research has shown the potential benefits to both patients and the country of regularly scheduled dialysis, so continued advocacy for undocumented patients with ESRD is needed to make sure they get the proper care they deserve.…”
Section: Meeting Challenges Of Ckd In Undocumented Immigrantsmentioning
confidence: 99%
“…Antiviral treatment for chronic HCV in posttransplant recipients costs $63 000 for a 12-week course early in disease progression and results in a sustained virologic response in >90%. 6 In contrast, hemodialysis incurs a cost of $77 000-400 000 annually. 7 Elbasvir/Grazoprevir is FDA approved for treatment of HCV genotypes 1 and 4 in patients with end-stage renal disease, achieving a sustained virologic response at 12 weeks in 95% of cases.…”
Section: Implications For Third-party Payersmentioning
confidence: 99%
“…The practice of emergency-only hemodialysis exists because hospitals can be reimbursed for these treatments under the Emergency Medical Treatment and Labor Act (EMTALA) of 1986, which mandated the provision of emergency care for uninsured individuals, including undocumented immigrants. 1,3 States such as California, New York, Illinois, and Washington offer standard hemodialysis therapy using nonfederal funds. In a recent qualitative study that explored the illness experience of undocumented immigrants with access to emergencyonly hemodialysis, patients described feeling distressed by the weekly accumulation of symptoms that trigger the emergency presentation to the emergency department, and many also described risking death by consuming foods high in potassium so that they would meet critically ill criteria for emergency-only hemodialysis.…”
mentioning
confidence: 99%